Mechanisms of compensatory dynamics in zooplankton and maintenance of food chain efficiency under toxicant stress - Mano, Hiroyuki (Ecotoxicology (London, England), 2016)
Communities with species that are tolerant to environmental stresses may be able to maintain the ecosystem functions under the stress, because the tolerant species can compensate for the loss of sensitive species. In this study, we focused on the food chain efficiency (FCE), the trophic transfer across three trophic levels, as an important process for ecosystem function, and examined the conditions under which such compensation could occur with aquarium experiments using an insecticide (methomyl) as the stressor. Our aquariums included one of two pairs of insecticide-tolerant and insecticide-sensitive cladoceran species, and a fish as the predator. The response of FCE to the insecticide stress, as indicated by the fish biomass production, depended on the zooplankton species combinations. FCE and total zooplankton biomass were maintained in the pair in which the compensatory changes of species abundances were clear, whereas they decreased in the pair in which the compensatory changes were not clear. This indicated the compensatory dynamics in the zooplankton community responsible for the observed resistance to the stress. We inferred the driving factors for the compensatory dynamics and the community resistance with respect to species traits of ecological importance, and concluded that a dissimilarity between species as regards the tolerance trait and a clear trade-off between the tolerance and the competitive ability was required to drive the compensatory dynamics, and a similarity or a superiority of the tolerant species as regards the functional effect trait (the predator avoidance and the reproductive potential) were required to maintain FCE